Perbedaan Pengetahuan Penanganan Dismenorea Sebelum Dan Sesudah Penyuluhan Pada Siswi Sekolah Menengah Pertama Santo Yoseph Denpasar - Angelina Felany Gandi; Made Widhi Gunapria Darmapatni (Poltekkes Kemenkes Denpasar, 2018)
The prevalence of dysmenorrhea is found to be quite high and varies, reaching 50% in each country and in Indonesia its self reaching out for 55%. Dysmenorrhea occured among productive ages including adolescents. The purpose of this research is to know the difference of knowledge of dysmenorrhea handling before and after counseling on the respondents. The type of this research is analytical research with One Group Pre-test design and Post-test Design. The knowledge of respondents is measured by using questioner and the hypothesis test using Paired Sample T-Test. The result of research of 69 respondents showed that before counseling scored of minimum knowledge of respondents is 20 and maximum scored is 80 with average scored 61,01. After counseling the minimum knowledge scored of respondents is 70 and the maximum scored is 95 with an average scored of 84.05. The result of different test of hypothesis found that p = 0.000 value less than 0,05 so it can be concluded that there is different knowledge of dysmenorrhea handling before and after counseling on respondents. Knowledge is the one important factor that supports the creation of effort to maintain health so it is necessary counseling to increase the knowledge possessed about handling dysmenorrhoea